Epigenetic Modification In Relation To Some Common Cancers - Adelola, Oluwatoyosi, Naomi; Olayemi, Rotimi, David; Adedoyin, Owolade, John-Joy; Opeyemi, Oladeru, Fortunate; Ado, Musa, Abba; Sheriff, Agbaje, Tunde; Seun, Ibrahim, John; Muinat, Zubair, Fehintola; Bello, Ridwan, Opeyemi; Adejo, Oche, Samuel; Nwankwo, Daniel, Ogbonnaya (My University, 2022)
Epigenetic modification is a process that regulates DNA sequences without altering the original structure of the DNA sequences. The distortion of DNA by epigenetic modification can turn gene expression off or on. Several scientific pieces of evidence have shown that the regular occurrence of a genetic mutation governed by epigenetic changes can subsequently usher in the onset of many diseases, including Cancer. DNA methylation and histone modifications, such as acetylation, methylation, and ubiquitination, which are well known to influence gene expression, are among the most frequent epigenetic changes. In this review, we ostensibly review epigenetic modifications and their relation to cancer development. We observed that many epigenetic changes in gene expression are actively linked to Cancer, and it remains one of the most potential areas in cancer research. Many epigenetic mutations are repeatedly detected in cancer research, and reversing these mutations in cancer cells can lead to the discovery of novel therapeutic approaches and cancer biomarkers.
Keywords: Cancer; DNA; DNA methylation; Epigenetics; Gene; Histone Modification; Non-coding RNA